Pengaruh Pemberian Edukasi Terhadap Penggunaan Antibiotik - nugraha, iwan saka (Jurnal Abdi Mahosada, 2023)
Self-medication is an effort made by someone to treat all complaints on themselves with medicines that are purchased freely at pharmacies or drug stores without using a doctor's prescription. Irrational use of antibiotics is often done in self-medication. Rational implementation of self-medication can increase public understanding of the use of antibiotics. The implementation method begins with giving a pre-test, continuing with giving education and closing with giving a post-test. The characteristics of the respondents above show that most of those who took part in this activity were aged 17-35 years by 60%. Most of them are female, 56% and most of them have high school education, namely 51%. The community has less knowledge (52%) regarding the proper use of antibiotics, there is an increase in post-test results, namely to 64%. Participants received information on how to store according to standards and there was an increase in knowledge about the use of antibiotics.